2017
DOI: 10.1007/s00520-017-3983-2
|View full text |Cite
|
Sign up to set email alerts
|

Meta-ethnography of experiences of early discharge, with a focus on paediatric febrile neutropenia

Abstract: Purpose (stating the main purposes and research question)Many children have no significant sequelae of febrile neutropenia. A systematic review of clinical studies demonstrated patients at low risk of septic complications can be safely treated as outpatients using oral antibiotics with low rates of treatment failure. Introducing earlier discharge may improve quality of life, reduce hospital acquired infection and reduce healthcare service pressures. However, the review raised concerns that this might not be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…The survey content was developed based on currently available literature, [17][18][19] expert clinician input, and parental review. It contained the following sections and number of closed statement items: Experiences (n = 6), Information (n = 7), Decisions (n = 7) and Support needs (n = 5) ( Figure 1…”
Section: Surveymentioning
confidence: 99%
“…The survey content was developed based on currently available literature, [17][18][19] expert clinician input, and parental review. It contained the following sections and number of closed statement items: Experiences (n = 6), Information (n = 7), Decisions (n = 7) and Support needs (n = 5) ( Figure 1…”
Section: Surveymentioning
confidence: 99%
“…Participants discussed many issues similar to those found in the earlier meta-ethnography. 11 Participants spoke of the tiring nature of travelling, particularly at night time or during the rush hour. Distance from the hospital played a key role in whether early discharge regimens would be accepted, with families living close to the treating hospital more likely to accept outpatient care.…”
Section: Resultsmentioning
confidence: 99%
“… 10 A meta-ethnography of the existing qualitative literature surrounding early discharge revealed that there may be challenges surrounding practical logistics, and social or emotional issues, influenced by fear, timing and resources. 11 However, the data focused almost exclusively on parental views, lacked exploration of the influence of healthcare settings and had little disease-specific data about febrile neutropenia.…”
Section: Introductionmentioning
confidence: 99%
“…The focus has moved to defining how narrow a spectrum of antibacterial can be safely used 12 and ways of discontinuing treatment quickly. Research has confirmed patients and their families want to be treated as safely as possible but get out of hospital as soon as they can to improve their life experience 13, 14 .…”
Section: Antibacterial Approachesmentioning
confidence: 99%